Analisa Faktor Pembentuk Karakteristik Sebaran Sarana dan Prasararana Permukiman Di Wilayah Perbatasan (Studi Kasus : Kelurahan Sendang Mulyo Kota Semarang) - olivia, deasy; Setioko, Bambang; Pandelaki, Edward Endrianto (Diponegoro University, 2018)
The urban development occurs through a process of sustainable urbanization. This process cause urban sprawl that spread until the outer part of the city known as the border area. Urban Sprawl encourage the growth of new sub-service facilities, especially in the border area of Semarang city. Sendang Mulyo village is a settlement that located in the border area of Semarang city and Demak region. Sendang Mulyo village has better urban infrastructure than the settlement in Demak. These conditions cause urban infrastructure serve not only the residents itself but also those who live outside of Semarang city. These phenomena is shape the urban infrastructure spreading characteristics in the border area. This article presents research in analysing 15 shaping factors of urban infrastructure spreading characteristics in the border area, in this case Sendang Mulyo Settlements Semarang City. Based on the results of this research which was conducted through positivistic paradigm and quantitative approach shows that the urban infrastructure spreading characteristics in the border area of Semarang city influenced by human aspect of the behaviour setting